Nitrogen fertilization effects on forage production and nutritive value of 4 tropical grasses on alkaline soils in Argentina - Mattera, Juan (2023)
This study evaluated effects of nitrogen (N) fertilization and gypsum application and their interactions on total pasture forage production and nutritive values of Chloris gayana cultivars ‘Santana’ and ‘Finecut’ and Panicum coloratum cultivars ‘Klein’ and ‘Bambatsi’ growing in a moderately sodic soil (Typic Natracualf) in northcentral Santa Fe Province of Argentina over 3 years. Sown pasture forage production differed among cultivars. C. gayana cultivar ‘Finecut’ produced more forage biomass than the other 3 cultivars. P. coloratum cultivars were superior to C. gayana cultivars for nutritive value, showing lower NDF and ADF. N fertilization strongly increased forage production, total biomass and sown pasture biomass with improved crude protein content and improvement in plant N status. Addition of gypsum did not affect forage production and nutritive value. This research showed the feasibility to improve production and nutritive value of tropical pastures in subtropical areas by species/cultivar selection and N fertilization.